THE INFLUENCE OF ALOEVERA CONCENTRATION ON MORPHOLOGY AND TENSILE PROPERTIES OF ELECTROSPUN ALOEVERA-PVA NANOFIBER - Harini Sosiati; Alif Nur Widodo; Aris Widyo Nugroho (Jurnal Sains Materi Indonesia, 2018)
THE INFLUENCE OF ALOE VERA CONCENTRATION ON MORPHOLOGY AND TENSILE PROPERTIES OF ELECTROSPUN ALOE VERA-PVA NANOFIBE. Aloe Vera (AV)-poly (vinyl alcohol)  (PVA) electrospinning solution with 0%, 2%, 4% and 6%AV concentrations were electrospun to explore the influence of AV concentration on the morphology and tensile properties of the nanofibers membranes. The results showed that the change in the morphology and tensile properties of electrospun AV-PVA nanofibers depends upon AV concentration of electrospinning solution. Mean fiber diameter at 2% (342 ± 0.8 nm) and 4% (337 ± 0.6 nm) AV concentrations is smaller than that at 0% (377 ± 1.1 nm) and 6% (810 ± 3.4 nm) AV concentrations with relatively uniform size distribution. Tensile strength and modulus at AV concentration of  2% (5.74 MPa and 33.99 MPa) and 4% (6.38 MPa and 34.75 MPa) are higher than that at 0% (4.98 MPa and 26.45 MPa) and 6% (2.22 MPa and 13.69 MPa), respectively. AV-PVA electrospinning solution with AV concentration ranging from 2% to 4% is considered being the optimum range that could produce the electrospun nanofibers with the tensile properties included in the range of that specified by the native skin.